Migration policies versus public health – the ethics of Covid-19 related movement restrictions for asylum seekers in reception centers in Greece in 2020 [version 3; peer review: 2 approved, 1 approved with reservations] - George Makris (Wellcome Open Research)
Background The emergency context of the Covid-19 pandemic necessitated the use of national and international public health measures of unprecedented scale to minimize mortality and morbidity, often in conflict with other principles and rights, such as the autonomy of individuals. Concerns have been voiced that for populations facing precarity, such as migrants, a disproportionate and unfair application of restrictive measures, deficient application of protective measures, and even enforcement of restrictive migration policies under the pretext of the pandemic has occurred. Methods Experts have proposed various principles as possible moral foundations of public health interventions. The author used two public health ethics frameworks to examine the ethical acceptability of movement restrictions on asylum seekers residing in refugee camps in Greece from March 2020 to October 2020. Results Most of the principles described in the frameworks for the ethical application of movement restrictions were not adhered to. Main concerns include that, measures were prolonged despite lack of evidence about their effectiveness to reduce morbidity and mortality, while posing severe and disproportionate burdens for this population. Conclusions An ethically acceptable public health response to Covid-19 is incompatible with certain living conditions of refugees, asylum seekers, and migrants. Moral and political determinants of health, such as social inequalities and criteria for health resources allocation, can shape the form and effectiveness of public health interventions during emergencies. The role of the discipline of public health to address these underlying determinants, that influence health-related outcomes, is an important moral question in itself. It is essential for public health professionals to be aware of the moral theorizations that underpin their work, so as to ensure that their policies align with them and to contribute to the debate that shapes these determinants.